Impact of Promotion and Service Quality on Tourists' Intention to Revisit Grand Elty Kalianda Beach - Wicaksono, FX Satrio; AA, Iskandar (BIMA Journal (Business, Management, & Accounting Journal), 2024)
Purpose: This study aims to analyze the effect of promotion and service quality on the interest of returning tourists to Grand Elty Kalianda Beach, Lampung. Methodology: The research employs quantitative methods. The population consists of tourists who visited Grand Elty Kalianda Beach in 2018, totaling 17,183 individuals. A sample of 100 tourists was selected. Data analysis was performed using Multiple Linear Regression analysis. Results: The findings indicate that both promotion and service quality significantly influence the interest of tourists in returning to Grand Elty Kalianda Beach. Findings: Promotion and service quality are key factors driving repeat visits by tourists to Grand Elty Kalianda Beach. Novelty: This research highlights the importance of targeted promotion and high service quality in increasing tourist loyalty to beach destinations. Originality: The study provides an empirical analysis of how promotional efforts and service quality affect tourist behavior in the context of a popular beach destination. Conclusions: Effective promotion and superior service quality are crucial in encouraging tourists to return to Grand Elty Kalianda Beach, Lampung. Type of Paper: Empirical Research Article.